Don't Just Judge the Spelling! The Influence of Spelling on Assessing Second-Language Student Essays - Thorben Jansen; Cristina Vögelin; Nils Machts; Stefan Daniel Keller (EARLI, 2021)
When judging subject-specific aspects of students' texts, teachers should assess various characteristics, e.g., spelling and content, independently of one another since these characteristics are indicators of different skills. Independent judgments enable teachers to adapt their classroom instruction according to students' skills. It is still unclear how well teachers meet this challenge and which intervention could be helpful to them. In Study 1, N = 51 pre-service teachers assessed four authentic English as a Second Language (ESL) essays with different overall text qualities and different qualities of spelling using holistic and analytic rating scales. Results showed a negative influence of the experimentally manipulated spelling errors on the judgment of almost all textual characteristics. In Study 2, an experimental prompt was used to reduce this judgment error. Participants who were made aware of the judgment error caused by spelling errors formed their judgments in a less biased way, indicating a reduction of bias. The determinants of the observed effects and their practical implications are discussed.